Effect of growing conditions on growth, flowering behaviour and seed yield of parental lines of pumpkin (Cucurbita moschata) cv. Pusa hybrid-I - FLEMINE XAVIER; BALRAJ SINGH; B.S. TOMAR (Seed Research, 2026)
The present investigation on parental lines of pumpkin (Cucurbita moschata Dutch Exploir.) cv. Pusa hybrid-1 was carried out at CPCT farm IARI, New Delhi during summer season under insect proof net (IPN) and open field Condition (OFC). The female line (seed parent) and male line (pollen parent) were transplanted in block method following the planting ratio of 3:1 at drip fertigation in IPN and OFC. Significantly higher vine length, number of leaf node on 30 days, 45 days from transplanting (DFT) and inter nodal length were recorded in seed and pollen parent. Days to first female and male flower opening in seed and pollen parent (56 days and 63.40 days, respectively) were significantly lower under IPN. The production of female flower (30.6/ plant) and male flower (40.3/plant) were significantly higher under IPN as compared to OFC. The number of fruits set (3.6) and matured fruit (3.5/plant were significantly higher under IPN than OFC (1.9 and 1.4, respectively). The incidence of pumpkin mosaic virus and insects were very low under IPN as compared to open field.